BoHV-4-based vector delivering Ebola virus surface glycoprotein. Issue 1 (December 2016) - Rosamilia, Alfonso; Jacca, Sarah; Tebaldi, Giulia; Tiberti, Silvia; Franceschi, Valentina; Macchi, Francesca; Cavirani, Sandro; Kobinger, Gary; Knowles, Donald; Donofrio, Gaetano
Abstract Background Ebola virus (EBOV) is a Category A pathogen that is a member ofFiloviridae family that causes hemorrhagic fever in humans and non-human primates. Unpredictable and devastating outbreaks of disease have recently occurred in Africa and current immunoprophylaxis and therapies are limited. The main limitation of working with pathogens like EBOV is the need for costly containment. To potentiate further and wider opportunity for EBOV prophylactics and therapies development, innovative approaches are necessary. Methods In the present study, an antigen delivery platform based on a recombinant bovine herpesvirus 4 (BoHV-4), delivering a synthetic EBOV glycoprotein (GP) gene sequence, BoHV-4-syEBOVgD106ΔTK, was generated. Results EBOV GP was abundantly expressed by BoHV-4-syEBOVgD106ΔTK transduced cells without decreasing viral replication. BoHV-4-syEBOVgD106ΔTK immunized goats produced high titers of anti-EBOV GP antibodies and conferred a long lasting (up to 6 months), detectable antibody response. Furthermore, no evidence of BoHV-4-syEBOVgD106ΔTK viremia and secondary localization was detected in any of the immunized animals. Conclusions The BoHV-4-based vector approach described here, represents: an alternative antigen delivery system for vaccination and a proof of principle study for anti-EBOV antibodies generation in goats for potential immunotherapy applications.